Reputation:
I have a goal which looks something like "\<forall>x. \<exists>y.\<forall>(z::real). P x y z"
. Is there a rule which immediately allows me to conclude "\<forall>x. \<exists>y.\<forall>(z::real). P x y (z-2)"
? If there isn't, I'd appreciate general advice on how to prove this type of goal.
I know I can prove it by using lots of allI
,exI
, allE
,exE
, but it seems like there must be a quick and simple way.
Upvotes: 2
Views: 102
Reputation: 2659
The following works in Isabelle2016-1-RC2:
lemma
assumes "∀x. ∃y.∀(z::real). P x y z"
shows "∀x. ∃y.∀(z::real). P x y (z-2)"
using assms by force
You can use the try0
command to give you a list of proof methods that are able to solve the goal.
Upvotes: 1